Determination of Maximum Accumulated Oxygen Deficit Using Backward Extrapolation - Andrade, Vitor Luiz [UNESP]; Kalva-Filho, Carlos Augusto; Ribeiro, Nayan Xavier; Gobbi, Ronaldo Bucken; De Arruda, Tarine Botta; Papoti, Marcelo (Thieme, 2021)
This study aimed to compare the Maximum Accumulated Oxygen Deficit determined by the conventional method (MAOD C) with that determined by the backward extrapolation technique (MAOD EXTR) in runners. Fourteen runners underwent a maximal incremental test for determination of iVO 2MAX, ten submaximal efforts (50-95% of iVO 2MAXfor 7 min). During the submaximal efforts oxygen consumption (VO 2) values were obtained conventionally and through the backward extrapolation technique (~ 3 s after the end of each effort). A supramaximal effort (110% of iVO 2MAX) (tLim C) and five supramaximal bouts (tLim EXTR) were performed. MAOD Cand MAOD EXTRwere determined from the difference between the VO 2accumulated during tLim Cand tLim EXTRand the predicted values. The tLim Cwas lower than tLim EXTR(164.06±36.32 s, 200.23±63.78 s, p<0.05). No significant differences were found between absolute and relative MAOD Cand MAOD EXTRvalues, however, low intraclass correlations (0.26 and 0.24), high typical errors (2.03 L and 24 mL · kg -1) were observed, and coefficients of variation (46 and 48%), respectively. The graphical analysis of the differences showed agreement and correlation between the methods (r=0.86 and 0.85). Thus, it can be concluded that the MAOD EXTRis not a valid method for estimating the anaerobic capacity of runners, moreover, unreliable.
Keywords: anaerobic capacity; anaerobic metabolism; MAOD; runners